2009
DOI: 10.1007/s10897-008-9205-9
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Cancer Surveillance Among High‐Risk Populations: Knowledge and Intent

Abstract: Pancreatic cancer is the fourth most common cancer in both men and women in the United States. It has the lowest survival rate of all cancers, largely due to the presence of non-specific symptoms, leading to diagnosis at advanced stages. While the majority of cases of pancreatic cancer are sporadic, up to 10% may be associated with an inherited predisposition. Currently, there is no standard screening protocol for pancreatic cancer, although this will change in the future as technology improves. Additionally, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 45 publications
2
21
0
Order By: Relevance
“…Comprehensive efforts are underway to better understand the etiology of PC, to improve treatment outcomes, and to develop and evaluate effective screening technologies [8,33]. Receptivity toward potential future screening options for pancreatic cancer among those at significant risk is an important, yet understudied area.…”
Section: Discussionmentioning
confidence: 99%
“…Comprehensive efforts are underway to better understand the etiology of PC, to improve treatment outcomes, and to develop and evaluate effective screening technologies [8,33]. Receptivity toward potential future screening options for pancreatic cancer among those at significant risk is an important, yet understudied area.…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies have been performed to evaluate the overall experience reported by individuals living with the knowledge that they are at increased risk of pancreatic cancer, 106,111 their knowledge of pancreatic cancer screening, 112 and their receptivity 113 or intent to engage in pancreatic cancer screening. Two qualitative studies focusing on patient experiences with pancreatic cancer risk 111 and understanding of and intent to engage in pancreatic cancer screening 112 found the family experience was an important factor in how someone viewed their own risk for pancreatic cancer and became motivated to engage in invasive screening.…”
Section: Hereditary/familial Pancreatic Cancermentioning
confidence: 99%
“…Two qualitative studies focusing on patient experiences with pancreatic cancer risk 111 and understanding of and intent to engage in pancreatic cancer screening 112 found the family experience was an important factor in how someone viewed their own risk for pancreatic cancer and became motivated to engage in invasive screening. Pancreatic cancer was considered a fatal disease 112 and therefore screening was viewed as a potential way to catch cancer early. 111 Participants had limited knowledge about the pancreas, pancreatic cancer, and screening, 112 and overall felt there was a lack of patient centered resources.…”
Section: Hereditary/familial Pancreatic Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Beside them, also members of a family with a strong history of disease or individuals with inherited pancreatic cancer syndromes, carrying a known genetic mutation, should be considered at high risk of developing pancreatic cancer (high risk individuals, HRIs) [21][22][23][24][25] . Screening of these high-risk groups seems to be of benefit since genetic susceptibility and familial aggregation are responsible of 3%-16% of pancreatic cancers [26][27][28] .…”
Section: Introductionmentioning
confidence: 99%